Beauty and the Beast - Ladybird (Italy Ladybird, 2006)
For over 40 years, the classic fairytale has delighted children and adults alike. This new Ladybird title combines a faithful retelling with rich, vibrant artwork, promising to reintroduce the magic of these timeless tales to those who loved them while casting a spell upon a new generation of readers.